2017
DOI: 10.1111/jbi.13092
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the climatic niche overlap of global sea turtle nesting sites: Impact of geographical variation and phylogeny

Abstract: Aim Identifying processes that determine climatic niche dynamics is difficult, especially for wide‐ranging species where niche conservatism might differ at different life stages. Evolutionary history shapes climatic niche, with populations of the same or phylogenetically close species occupying similar conditions. However, the geographical separation of populations also leads to niche evolution as an adaptive response to local conditions. Here, we use five sea turtle species (loggerhead, green, leatherback, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…Third, we found support for increased niche tracking in species with larger range sizes but no support for increased niche tracking with wider niche breadth. Large range sizes increased the probability of finding comparable environments in opposing seasons for both predictor sets which is in line with previous findings on migratory sea turtle species (Almpanidou, Schofield, & Mazaris, ). Such a positive effect of range size, after controlling for statistical bias through similarity tests, could indicate other biotic controls on seasonal niche tracking.…”
Section: Discussionsupporting
confidence: 91%
“…Third, we found support for increased niche tracking in species with larger range sizes but no support for increased niche tracking with wider niche breadth. Large range sizes increased the probability of finding comparable environments in opposing seasons for both predictor sets which is in line with previous findings on migratory sea turtle species (Almpanidou, Schofield, & Mazaris, ). Such a positive effect of range size, after controlling for statistical bias through similarity tests, could indicate other biotic controls on seasonal niche tracking.…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, under the assumption of climatic niche conservatism, another recent study suggested that turtle species richness and distribution may decrease as a result of climate change affecting species' climatic niches (Ihlow et al., ). However, no previous study has evaluated climatic niche evolution for the whole group of nonmarine turtles (but see Almpanidou, Schofield, & Mazaris, for a general evaluation of niche conservatism in sea turtles) and climatic niche comparisons conducted so far have been mainly focused on invasive species (Liu et al., ; Rödder, Schmidtlein, Veith, & Lötters, ; Rodrigues, Coelho, & Diniz‐Filho, ; Rodrigues, Coelho, Varela, & Diniz‐Filho, ) with mixed results of niche conservatism and shifts. Therefore, studying niche evolution patterns in turtles represents an interesting opportunity with theoretical (understanding whether species habitat could influence climatic niche evolution) and conservation (understanding whether turtles could be able to deal with anticipated climatic changes) implications.…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrate the need for conservation of sites that have key critical foraging habitat for two imperiled sea turtle species (following on Hart et al, 2012). Lastly, another set of major threats not included in this analysis are those currently occurring and predicted from climate change (e.g., Almpanidou et al, 2017). It will be important to track changes and shifts in both sea turtle habitat-use patterns and threat levels in these and other sea turtle foraging "hot spots" as well as to assess how impact weights of existing threats may fluctuate due to climate change in the future.…”
Section: Resultsmentioning
confidence: 78%